THE IMPACT OF TOURISM ACTIVITIES ON LAND USE BASED ON FORMAL LAW AND TRADITIONAL LAW (CASE STUDY: CANGGU VILLAGE, BALI) - Athaya Putri, Titania
Bali Island, an icon of Indonesian tourism, is famous for its natural beauty, art, and culture that attract tourists from around the world. The development of tourism in South Bali, particularly in Canggu Village, has had a significant impact on land use. Canggu Village, initially an agricultural area with green land, has now transformed into a location for tourism accommodation such as villas and hotels, driven by the increasing demand from tourists for such facilities. This research aims to identify the influence of tourism on land use changes in Canggu Village and the compatibility of these changes with formal and customary laws. Data was collected through qualitative-descriptive methods, including interviews, observations, and document analysis using NVIVO 14 software. The analysis includes identifying tourism development, the process of land use changes, and the compliance of land use with formal and customary laws. The research results indicate that tourism has caused a shift in land use from agriculture to accommodation, reducing productive agricultural land and threatening local food security. According to formal law, land use changes are regulated by the Regional Spatial Planning (RTRW) and Detailed Spatial Planning (RDTR), but the implementation often does not align with the plan. Customary law, through the village's awig - awig(customary rules), also plays a crucial role in controlling land use based on the Tri Hita Karana philosophy, which emphasizes balance between humans, God, and the environment. However, customary law faces challenges in maintaining the balance between development needs and the preservation of culture and the environment. The research identifies driving factors such as economic development, infrastructure development, development policies, and investment, as well as inhibiting factors like environmental regulations, land conflicts, and infrastructure limitations. In conclusion, the development of tourism in Canggu Village has a significant impact on land use, which does not always align with formal and customary laws. Comprehensive and integrative policies are needed to maintain the balance between tourism development and the preservation of green land and local culture.